Implementación de un sistema de información para la gestión de historiales médicos en la Clínica San Camilo Salud, Tarapoto - Villegas Mera, Carla Saith (2015)
This thesis is the result of applied to solve the problem in order to carry out proper management of medical records in clinical research San Camilo Salud Tarapoto. This information technology provide a viable and sustainable solution to allow the Medical Director -General and the heads of each area of expertise provided to monitor and direct product best strategies for better decision making. The Directors and Senior Staff of the institution aims to improve the care and monitoring of various diseases to patients admitted for day different diseases or medical emergencies , generating a medical history that will reveal in detail the treatment and monitoring of patients. Thanks to the information provided and opinions made possible improvements in the approach to this project. Own different stages of modeling and software development in web environment with reporting requirements suggested by the owners of the problem was made. Two types of information differed in system architecture: Operation and Management, the latter being very important in meeting the objective of this research. Finally, the software was developed using technological tools such as modelers and programming language, which once completed successfully generated. Thanks to this technological project management process Medical Records which currently allow a better route decision making at Board and senior staff was optimized.